Análise crítica-reflexiva sobre minha graduação no curso de medicina da UFSCar - Ueda, César Nathan Shoji (Universidade Federal de São Carlos, 2025)
This paper aims to discuss the skills developed through problem-based learning in theoretical and practical settings, from the perspective of curricular development, integration with the São Carlos healthcare network, and the challenges posed during the undergraduate program. It also considers the adaptation of a fundamentally practical course to the quarantine context of the largest pandemic in recent history. The narrative will be presented chronologically in cycles that represent the different stages of medical training through the UFSCar medical course.
Critical-reflexive analysis about my undergraduation in medicine at UFSCar
Keywords: Aprendizagem Baseada em Problemas; Educação médica; CIENCIAS HUMANAS::EDUCACAO::CURRICULO; 4. Educação de Qualidade